Association between psychosocial, organizational and personal factors and prevalence of musculoskeletal disorders in office workers. Issue 2 (2nd April 2016) - Piranveyseh, Peyman; Motamedzade, Majid; Osatuke, Katerine; Mohammadfam, Iraj; Moghimbeigi, Abbas; Soltanzadeh, Ahmad; Mohammadi, Heidar
Abstract : The purpose of this study was to investigate the relationship between organizational and personal (individual) factors with the prevalence of musculoskeletal disorders (MSDs) in office workers of the Iranian Gas Transmission Company. The participants rated two questionnaires – the standardized Nordic Musculoskeletal Questionnaire to measure the prevalence of MSDs, and the Veterans Healthcare Administration All Employee Survey questionnaire (2004 version) – to measure psychosocial, organizational and individual aspects of job satisfaction and workplace climate. The highest prevalence of MSDs was found in the lower back (49.7%) and neck (49.0%) regions. Results of the logistic regression models showed that some psychosocial and organizational factors and also some individual factors were associated with prevalence of MSDs ( p < 0.05).These ﬁndings illustrate the need to consider all elements of the work system as a whole in future studies and in organizational planning.